The Lymphoid Tissue Pharmacokinetics of Tenofovir Disoproxil Fumarate and Tenofovir Alafenamide in HIV‐Infected Persons. Issue 5 (11th June 2020) - Fletcher, Courtney V.; Podany, Anthony T.; Thorkelson, Ann; Winchester, Lee C.; Mykris, Timothy; Anderson, Jodi; Jorstad, Siri; Baker, Jason V.; Schacker, Timothy W.
Abstract : The secondary lymphoid tissues (LT), lymph nodes (LN) and gut‐associated lymphoid tissue are the primary sites of HIV replication and where the latent pool of virus is maintained. We compared the pharmacokinetics of tenofovir disoproxil fumarate (TDF) and tenofovir alafenamide (TAF) in LT of 13 HIV‐infected persons receiving a TDF‐containing antiretroviral regimen who subsequently switched to a TAF‐containing regimen. Study participants were on stable antiretroviral therapy for ≥12 months with plasma HIV‐RNA < 48 copies/mL for 6 months before enrollment and entry CD4 cell counts > 300 cells/µL. Intracellular concentrations of tenofovir‐diphosphate (TFV‐DP) and emtricitabine‐triphosphate (FTC‐TP) were quantified in PBMCs and in mononuclear cells obtained from LN, ileum and rectal tissues. With TAF, the TFV‐DP concentrations in PBMCs and LN were 7.3‐fold and 6.4‐fold higher (ratios of geometric means of TAF to TDF), respectively, compared with TDF; ileal and rectal concentrations, however, were lower with geometric mean ratios of 0.14 and 0.18, respectively. A statistically significant relationship was observed between PBMC and LN concentrations of TFV‐DP. During TDF‐containing therapy, the expected effect of cobicistat to increase TFV plasma concentrations was observed, as were higher TFV‐DP concentrations in PBMCs and mononuclear cells from LN, ileum and rectal tissues. The higher TFV‐DP concentrations achieved with TAF in the LN provides the first human correlate of the observation in animals that TAF produced higher tenofovir LN concentrations. The ability to increase LN concentrations allows investigations of whether antiretroviral regimens with improved LN pharmacokinetics elicit a more complete virologic response in that compartment.